'Strange multiplicity' as a moral-political value: Potential and costs of normativity in world politics. (October 2022) - Royer, Christof
Recent International Relations (IR) scholarship has identified 'societal multiplicity' as the ontological concept that gives IR its identity as an academic discipline. My article, by contrast, addresses the question: What are the consequences, that is, the positive potential and the necessary costs, of understanding multiplicity as a moral-political value in world politics? The question is important because, in contrast to the focus on multiplicity as the ontology of IR, it allows us to develop a more radically democratic idea of multiplicity as a value in world politics. To address this question, I will bring Rosenberg's conception of societal multiplicity into conversation with the radically democratic idea of Tully's 'strange multiplicity' and draw out the consequences of such a normative turn. My argument is that while Rosenberg does not frame multiplicity as a value, Tully's normative understanding of the concept harbours enormous potential to transform oppressive and dominating practices in world politics. However, I will also show that Tully's general rejection of all forms of domination comes at a price that must not be underestimated. It is of crucial importance to get a clear picture of these consequences as we must decide whether or not this price is, ultimately, worth paying.